The story of country - Sagar, Lindsey (San Diego, CA : Silver Dolphin Books, an imprint of Printers Row Pub. Group, a division of Readerlink Distribution Services, LLC, 2020)
Presents an illustrated look at different country musicians from Dolly Patron, Johnny Cash, Willie Nelson and others for young readers.
Cover title.
On board pages.
Preschool.
Preschool
Keywords: Board books -- Specimens; Country music -- Juvenile literature; Country musicians -- Juvenile literature; Women country musicians -- Juvenile literature; Musicians; Board books; Country music; Country musicians; Women; Board books for children; Country music; Country musicians; Musicians; Women